Comparative Efficacy and Safety of Baricitinib Against Traditional Therapies in Severe Alopecia Areata: A Retrospective Cohort Study - Stefanis, Athanasios J; Dolezal, Tomas; Gkalpakiotis, Spyridon; Arenberger, Petr (Journal of cosmetic dermatology, 2025)
INTRODUCTION: Alopecia areata is a common autoimmune disease which results in reversible hair loss. Janus kinase inhibitors are prescribed for severe alopecia areata with encouraging results. There are no studies comparing the efficacy and safety of Janus kinase inhibitors to traditional treatment options, such as topical immunomodulators and traditional immunosuppressants. AIMS: To retrospectively compare the efficacy and safety of baricitinib, an approved Janus kinase inhibitor, to other treatments for severe AA during a 6-month treatment period. MATERIALS/METHODS: We included patients with newly presenting, relapsing or treatment-resistant alopecia areata with Severity of Alopecia Tool (SALT) score ≥ 50, for the period between July 2021 and July 2023. Medical histories were reviewed and possible side effects were recorded. Primary endpoints were SALT ≤ 20 and SALT ≤ 10 after 6 months of treatment. RESULTS: Seventy-five patients (53 females) were divided into three groups: topical immunomodulators (51 patients); baricitinib (19 patients); and a group receiving pulsed intramuscular corticosteroids or traditional immunosuppressants (11 patients). Twenty-one patients received more than one treatment options within 2 years. After 6 months, the baricitinib group showed superior efficacy with 32% and 26% of patients achieving SALT ≤ 20 and SALT ≤ 10, compared to 12% and 9% in both other groups. Baricitinib demonstrated better secondary outcomes (50% and 90% reduction from initial SALT scores). All treatments exhibited mild-to-moderate and expected side effects. Weight gain, which had not been reported in clinical trials for alopecia areata, was observed in three baricitinib-treated patients. CONCLUSION: Baricitinib was superior to traditional treatments for severe alopecia areata after 6 months. Weight gain concerned 16% of patients receiving baricitinib.
Keywords: pyrazoly; Alopecia Areata; JAK inhibitors; Humans; lidé středního věku; Azetidines; azetidiny; alopecia areata; Female; mladý dospělý; dospělí; sulfonamidy; Purines; výsledek terapie; lidé; baricitinib safety; imunosupresiva; Adult; Immunosuppressive Agents; Janus Kinase Inhibitors; inhibitory Janus kinas; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; Retrospective Studies; Adolescent; Treatment Outcome; puriny; baricitinib; Severity of Illness Index; Young Adult; retrospektivní studie; baricitinib efficacy; mužské pohlaví; Pyrazoles; Sulfonamides; mladiství